Community-oriented Sharing Platforms in Space 4.0. Issue 1 (June 2020) - Marin, A; Alonso, I; Romeo, A; Patruno, J; Barchetta, F; Leonardi, M; Sacramento, P; Landgraf, G; Vermeulen, E P M
Abstract: Space 4.0 will bring an enormous wealth of data about our Earth that needs to be well exploited. But how do we bring this wealth to citizens? Space 4.0 is also about the best use of Big Data approaches and the use of the digital information economy as a powerful tool to bring information to citizens. Digital platforms have to excel on 3 main pillars [1]: Technology, Content and Culture. The Thematic Exploitation Platforms (TEPs) are operational today for the Urban, Forestry, Coastal, Hydrology, Food Security, Polar & Geohazards communities. These platforms provide scientists, commercial operators and citizens with an environment where they can share their questions, analysis, results through their investigation, algorithms, products to find new solutions for a better and safer world.